Pengaruh Pandemi Covid-19 Terhadap Angka Perceraian di Pengadilan Agama Kota Makassar - Jumliadi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study investigates the impact of the COVID-19 pandemic on the divorce rate at the Makassar City Religious Court. Employing a quantitative correlational approach, the research involved 107 divorce cases occurring during the pandemic, selected using a purposive sampling technique. Data were collected via questionnaires and analyzed using SPSS. Descriptive analysis results indicate that both the impact of the COVID-19 pandemic (mean 3.88; 63%) and the divorce rate (mean 3.79; 69%) are categorized as high. Inferential analysis, with a significance value of 0.000<0.05, confirms a significant influence of the COVID-19 pandemic on the divorce rate at the Makassar City Religious Court, supported by both theoretical and empirical findings.